Studi Penempatan Titik Pentanahan Kawat Tanah Pada Penyulang Serangan - Baskara, I Wayan Agus Teja; Arjana, I G Dyana; Rinas, I W (Majalah Ilmiah Teknologi Elektro; Vol 15 No 1 (2016): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2016.v15i01p05, 2016)
Ground wire is one of the lighning protection instrument used in medium voltage distribution network with the intention to reduce interference due to lightning strikes. On the feeder Serangan the ground wire put 4 – 5 wicket. To know effective gap of ground wire is put on the feeder Serangan then used effectiveness ground wire parameters and total of disorder by lightning strikes directly or indirectly. From the analysis is obtained the effective gap on scenario 4 by 3 – 4 wicket. Choosing scenario 4 is as effective gap because seen by economic aspect, as longest gap point put of ground wire then the cost needed to use material and the installation of ground wire will be cheaper.   DOI :  10.24843/MITE.1501.05
Keywords: ground wire , lightning strikes , wave walk